Tailoring microstructure and microhardness of Zn−1wt.%Mg−(0.5wt.%Mn, 0.5wt.%Ca) alloys by solidification cooling rate - VIDA, Talita A. (2021)
Biodegradable Zn-based alloys, particularly Zn−Mg alloys with the addition of alloying elements, have been intensively investigated aiming to improve both mechanical properties and corrosion behavior. Since such properties are strongly dependent on the alloy microstructure, any evaluation should commence on understanding the conditions influencing its formation. In this study, the effect of the solidification cooling rate on the microstructural evolution of Zn−1wt.%Mg−(0.5wt.%Ca, 0.5wt.%Mn) alloys during transient solidification was investigated. The results show that the microstructures of both alloys have three phases in common: η-Zn dendritic matrix, intermetallic compounds (IMCs) Zn11Mg2, and Zn2Mg in the eutectic mixture. MnZn9 and two Ca-bearing phases (CaZn11 and CaZn13) are associated with Mn and Ca additions, respectively. These additions are shown to refine the dendritic matrix and the eutectic mixture as compared to the Zn−1wt.%Mg alloy. A correlation between cooling rate, dendritic or eutectic spacings was developed, thus permitting experimental growth laws to be proposed. Additionally, hardness tests were performed to evaluate the effects of additions of Ca and Mn. Experimental correlations between Vickers microhardness and secondary dendritic spacings were proposed, showing that the microstructural refinement and characteristic Ca and Mn based IMCs induce an increase in hardness as compared to the binary alloy.